Optimal Timing of Tracheostomy in Critically Ill Adults Requiring Prolonged Mechanical Ventilation: An Updated Meta-Analysis of Randomized Controlled Trials - Fauzul Nurul Azmi; Novita Anggraeni; Johannas; Wan Novriza Wijaya (HM Publisher, 2026)
Background: Tracheostomy is among the most frequently performed procedures in the intensive care unit (ICU), yet the optimal timing relative to the onset of invasive mechanical ventilation remains contested. This study aimed to provide an updated quantitative synthesis of randomized controlled trials (RCTs) comparing early versus late tracheostomy in critically ill adults, incorporating the two most recent landmark trials. Methods: PubMed was systematically searched, supplemented by reference-list screening, for RCTs comparing early with late tracheostomy in mechanically ventilated adults. Study selection and data extraction were performed independently and in duplicate. Risk of bias was appraised with the Cochrane RoB 2 tool and the certainty of evidence with the GRADE framework. Dichotomous outcomes (all-cause mortality, ventilator-associated pneumonia [VAP]) were pooled as risk ratios (RR); continuous outcomes (duration of mechanical ventilation, ventilator-free days) as standardized mean differences (SMD, Hedges’ g), using a DerSimonian–Laird random-effects model. Results: Nine RCTs enrolling 2,500 critically ill adults were included. Early tracheostomy was not associated with reduced all-cause mortality (RR 0.88, 95% CI 0.70–1.09; p=0.24; I²=58.9%; prediction interval 0.48–1.59; seven trials; moderate certainty). A non-significant trend towards fewer VAP episodes was observed (RR 0.67, 95% CI 0.42–1.05; p=0.08; I²=71.0%; four trials; low certainty). Early tracheostomy showed non-significant tendencies towards a shorter duration of mechanical ventilation (SMD −1.38, 95% CI −3.44 to 0.68; I²=97.2%) and more ventilator-free days (SMD 0.20, 95% CI −0.07 to 0.47). Leave-one-out and Hartung–Knapp–Sidik–Jonkman analyses confirmed the robustness of the neutral mortality finding. Conclusion: In critically ill adults requiring prolonged mechanical ventilation, early tracheostomy did not significantly reduce mortality and conferred, at most, modest and uncertain benefits on VAP and ventilation-related resource use. Timing should remain an individualized clinical decision rather than a uniform protocol.